The Role of Corporate Strategy On Compliance With Government Regulations Among Saccos In Kenya - Okibo, Bichanga Walter; Chepkwei, Ambrose Kipruto (Journal of Research in Marketing (ISSN: 2292-9355), 2013)
Saving and Credit Cooperative societies are financial service providers and their services include receiving deposits, multiplying the same by a factor in order to grant loans, receiving cash deposit and making payments inform of cash withdrawals. The creation of a regulator, the SACCO Society Regulatory Authority (SASRA) to supervise all deposit taking savings and Credit Cooperative Societies (SACCOs) was received with mixed feelings within the industry. While the new regulatory environment promises to calm the nerves of the SACCO members who now have their savings under close supervision, there has been disquiet in the industry from a number of big societies. There is lack of an in-depth understanding of the cooperative Act and regulation in most SACCOs to integrate the regulatory requirements in the corporate strategy and operational policies for day-to-day running of the SACCO. The objectives of the study included: to assess the role of stability strategies on compliance with government regulations in SACCOs; to evaluate the role of concentration strategy of SACCO on compliance with government regulations and to examine the role of diversification strategy and on compliance with government regulations in SACCOs. The study was carried out in Baringo Teachers SACCO head office and its seven FOSA branches in Baringo County - Kenya. It involved a population of 86 employees of Baringo Teachers SACCO from which a sample 40 was drawn using purpose sampling techniques. The findings of the study indicate that there exist corporate strategies in SACCO and roles of corporate strategy were highlighted in the study. The compliance on government regulations resulted in tax compliance, timely reports and protection of members’ funds, something that was confirmed by most managers. The research also revealed the role of diversification strategy of products and services in SACCOs.